2012
DOI: 10.5851/kosfa.2012.32.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin M1 in Pasteurized Market Milk in Korea

Abstract: Aflatoxin M1, ingested as aflatoxin B1 via contaminated feedstuff and later converted into, is a major problematic target for milk safety control among the aflatoxin class. Korean government has controlled level of AFM1 in milk at 500 ppt as maximum residue level (MRL), and more recently, government also publicized the proposal for more strict control on fungal toxins about infant and baby foods. In this study the levels of Aflatoxin M1 (AFM1) of 42 marketed milk samples were determined with Enzyme-Linked Immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…According to previous studies, the milk sterilization method affects AFM 1 concentration in milk. AFM 1 concentrations in pasteurized milk have been shown to be higher than those of raw and UHT milk (Hwang, Hwang, Kim, & Oh, 2012;Kocasari et al, 2012;Zheng et al, 2012). In this study, pasteurized milk had higher mean values of AFM 1 and AFM 2 concentrations than UHT milk.…”
Section: Afm 1 and Afm 2 Contamination Levels In Milk Yogurt Milk Pmentioning
confidence: 42%
“…According to previous studies, the milk sterilization method affects AFM 1 concentration in milk. AFM 1 concentrations in pasteurized milk have been shown to be higher than those of raw and UHT milk (Hwang, Hwang, Kim, & Oh, 2012;Kocasari et al, 2012;Zheng et al, 2012). In this study, pasteurized milk had higher mean values of AFM 1 and AFM 2 concentrations than UHT milk.…”
Section: Afm 1 and Afm 2 Contamination Levels In Milk Yogurt Milk Pmentioning
confidence: 42%
“…During fermentation, most of the monosaccharides were used by LAB as carbon sources, so the monosaccharide content reduced markedly. Where enzymolysis also occurred during LAB fermentation, for example, it is reported that L. rhamnosus was able to produce a high beta-glucosidase 28,29 activity, which could further decompose macromolecule sugars in the matrix. Therefore, the polysaccharide content was further decreased, and the oligosaccharide content increased, supplied by the polysaccharides.…”
Section: The Inuence Of Lactic Acid Fermentation On Oligosaccharide ...mentioning
confidence: 99%
“…4 The risk of AFM1 in milk is a major concern due to the high daily consumption rates of milk worldwide. [5][6][7] The tolerance level for AFM1 in milk products has been set at 0.5 mg L À1 (Chinese National Standard GB2761). Immunoassay, is a sensitive, low-cost and fast detection technique that has been reported to detect AFM1.…”
Section: Introductionmentioning
confidence: 99%